The Role of Constitutional Judiciary In Activating The Legal Responsibility of The Resigned Government (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract It is known that the subject of the resigned government is one of the most important topics of public law, especially in constitutional law, and the importance of the subject comes through the phenomenon of political instability witnessed by the Arab countries, to find this theory of its competences in this field, as well as the danger of not knowing researchers in the academic community specialized in the field of constitutional law with its provisions, despite its treatment by some Arab constitutions, in exchange for what the French and Belgian judiciary enriched legal studies in this The field, has raised a great controversy in jurisprudence about the existence of this theory in terms of the basis, some of them have found that the resigned government remains present like the regular governments that exercise their actual role in governance, and can not be viewed from a narrow perspective by restricting them in the scope of the urgent caretaker, the dissolution of parliament may be a motive for its work in the absence of parliamentary oversight.If this theory aims to limit the competence of the resigned government to a certain scope, namely the conduct of business, it is necessary to achieve full control of its work by specialized bodies to ensure that it does not exceed the limits of its competencies in order to preserve the supremacy of the principle of legality, in exchange for ensuring the proper application of laws and the basic law from which it draws from, which is the constitution. It is the subject of our research which so-called: "The Role Of Constitutional Judiciary In Activating The Legal Responsibility Of The Resigned Government".Key words : Resigned government- Judicial control- Constitutional judiciary- Legal Responsibility- Constitution.